The Impact Of Village-Owned Enterprises (Bumdes) In Strengthening Local Economy In The Border Village Of Sebente, Bengkayang Regency - Blasius Manggu; Sabinus Beni (Fakultas Bisnis, 2020)
In an effort to improve the welfare of the community as a non-governmental organization and see the potential it has, as well as the needs of the community, the presence of